Pengaruh Faktor Bangsa, Berat Badan, Harga Dan Jenis Kelamin Sapi Potong Terhadap Bobot Karkas - Rismandiri -Rismandiri; Euis Dasipah; Tuti Gantini (Fakultas Pertanian Universitas Winaya Mukti, 2023)
The demand for beef for consumption by the Indonesian people, which is increasing every year, is met through the production of local meat and imported meat. The government's efforts through the meat self-sufficiency program encourage the private sector to increase the beef cattle population by bringing in imported cattle. The physical condition of a larger cow will produce a lot of meat. The purpose of this study was to analyze the factors of race, weight, price and sex of cattle correlated with carcass weight. The research method used is descriptive verification method with a quantitative approach. Variables calculated include nation, body weight, price, sex and carcass weight of cattle. To determine the relationship between the variables, the analysis used was parametric and non-parametric analysis. The results of the study based on the ANOVA test showed that the breed of cattle to the average carcass weight was significantly different (P <0.05), so it needed to be tested further using Tamhane. The results showed that heifer and bull cattle were not significantly different from carcass weight. Gender was not significantly different from carcass weight (P<0.05), cattle prices were significantly different from carcass weight (P>0.05) and cattle body weight was not significantly different. significantly to carcass weight (P<0.05).